Metode Pengajaran Bahasa Bali dalam Gending Baris Dadap di Desa Sukawana Kintamani Bangli - Arnama, Dewa Gede; Desi Sentana, Gek Diah; Ranem, I Nyoman (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
One of the traditional poems that is still used today is the gending baris dadap in Sukawana Village Kintamani Bangli. This song is formed with beautiful words. The existence of the gending baris dadap in Sukawana Village is still sustainable and maintained today in the midst of the progress of the times. This indicates that there is a teaching method or process used to preserve it. Of course, the efforts to preserve the gending baris dadap cannot be separated from the process of teaching the Balinese language. In this research, there are three formulations of the problem, briefly taking the issue of: What is the structure, teaching methods, and the meaning of the gending baris dadap in Sukawana Village, Kintamani Bangli? This research aims to describe the structure of the gending baris dadap, the teaching methods used in the gending baris dadap, and the meanings of the gending baris dadap in Sukawana Village, Kintamani Bangli. The theories used are structural theory, behavioristic learning theory, and semiotic theory. Data collection techniques to collect data in the form of: observation, interviews, documentation, and literature study. The results of this research are the structure of the gending baris dadap in Sukawana Village, Kintamani Bangli consisting of; diction, imagination, rhythm, figurative language, taste, theme, character, and message. The Balinese language teaching methods used are the direct method, reading method, audio-lingual method, drilling method, and imitation method. The content of meaning in this gending baris dadap is religious meaning, socio-cultural meaning and entertainment meaning.